Electricity markets and power system economics - Gan, Deqiang 1966-; Feng, Donghan 1966-; Xie, Jun (CRC Press, 2014)
With the theories and rules of electricity markets developing rapidly, it's difficult for beginners to start learning and difficult for those in the field to keep up. Bringing together information previously scattered among various journals and scholarly articles, this book provides a comprehensive overview of the current state of development in the electricity market. It introduces the fundamental principles of power system operation so that even those with a basic understanding can benefit from the book. It includes a series of consistent mathematical models of market operation of power systems, original cases, and MATLAB programming examples with solutions